Identificação dos casos de school shooting no Brasil - Cordeiro, Douglas (Universidade Federal de São Carlos, 2024)
School shooting is an English term that encompasses attacks, fatal or not, where one or more individuals aim to murder several people in a school or university where they were previously associated. This research aimed to identify school shooting cases that occurred in Brazil in the last 30 years through the analysis of journalistic materials. After searching the digital archive of Grupo Globo's online platforms, 44 cases were selected for analysis. The results indicated that the majority of cases (72.7%) occurred between 2019-2023, in the Southeast region (65%), in public schools (86.7%) at the elementary and high school levels (93.3%). In total, 139 people were directly affected, 102 injured, and 37 killed. Of the victims, 75.2% were students, and 51.5% were female. All perpetrators (n=45) were male, with ages ranging from 9-39 years (M=16.7; SD=5.2), 71.4% were students, and 26.1% were former students of the institution. In the majority of cases (54.6%), bladed weapons were used. Firearms accounted for the highest number of victims (n=88) and fatalities (n=35). The discussion explores the variables that may have contributed to the occurrence of these cases and possibilities for preventing the phenomenon.
Brasil's school shooting cases identification
Keywords: Violência; Violence; School violence; Violência escolar; Escola; School; CIENCIAS HUMANAS::PSICOLOGIA::TRATAMENTO E PREVENCAO PSICOLOGICA